The importance of own learning style knowledge for students of the basic skills area from the foreign language department - González Garay, Rut del Carmen; López de Marroquín, Patricia del Carmen; Ayala, Edgar Nicolás; Salazar Murcia, Pedro Antonio (San Salvador : Universidad de El Salvador, 2003)
Considering the important role that “Learning Styles” play for second language students during their learning process and also for teachers of English , this essay is focused on the students from the Foreign Language Department, specifically on students from the Basic Skills Area. This essay sustains the thesis that “The lack of explicit knowledge of own learning styles of students from the Basic Skills Area affects second language acquisition” and it is supported by bibliographical sources as well as by information derived from a learning style inventory and a questionnaire administered to the sample of students from the mentioned area. The information presented in the essay is really valuable since it will serve to teachers and students realize the influence of this topic in the learning and teaching process of a second language.
Incluye anexos
Tesis (Licenciatura en Idioma Inglés opción enseñanza) -- Universidad de El Salvador, San Salvador, 2003
Bibliografía : h. 28-31
Keywords: Ingles -- Enseñanza; Aprendizaje verbal; Inteligencia